Una arquitectura de software para la gestión de historias clínicas electrónicas soportada en tecnologías web - Diosa, Henry Alberto; Isaza Peña, Carlos Andrés; Buenhombre González., Teresa (Ingeniería, 2001)
Among the activities that it comes carrying out, the CORBA-OSM group has assumed the development of some degree projects that explore the potential of Web technologies. The supported management system of Electronic Clinical Histories in Web Technologies is an application that looks for to outline a possible support to the treatment and administration of the clinical histories inside a "Institución Prestadora de Servicios de Salud (IPS)", specifically in the mark of the general medical consultation or external consultation, by means of the use of software tools that rotate around the WEB, such as: Java, JSP (Java Server Pages), XML (Extensible Markup Language) and their related technologies.